n‐butylidenephthalide treatment prolongs life span and attenuates motor neuron loss in SOD1(G93A) mouse model of amyotrophic lateral sclerosis - Zhou, Qin‐Ming (CNS Neurosci Ther, 2017)
AIMS: To evaluate the therapeutic effects of n‐butylidenephthalide (BP) in SOD1(G93A) mouse model of amyotrophic lateral sclerosis and explore the possible mechanisms. METHODS: The SOD1(G93A) mice were treated by oral administration of BP (q.d., 400 mg/kg d) starting from 60 days of age and continuing until death. The rotarod test was performed to assess the disease onset. The expression levels of apoptosis‐related proteins, inflammatory molecules, and autophagy‐associated proteins were determined. The number of apoptotic motor neurons and the extent of microglial and astroglial activation were also assessed in the lumbar spinal cords of BP‐treated mice. Grip strength test, hematoxylin‐eosin staining, nicotinamide adenine dinucleotide hydrogen staining, and malondialdehyde assay were conducted to evaluate the muscle function and pathology. RESULTS: Although BP treatment did not delay the disease onset, it prolonged the life span and thereafter extended the disease duration in SOD1(G93A) mouse model of ALS. BP treatment also reduced the motor neuron loss through inhibiting apoptosis. We further demonstrated that the neuroprotective effects of BP might be resulted from the inhibition of inflammatory, oxidative stress, and autophagy. CONCLUSION: Our study suggests that BP may be a promising candidate for the treatment of ALS.